HAKIKAT DAN KONSEP SEHAT PADA KESEHATAN GIZI ANAK USIA DINI - Nurliyah Nasution; Yusniarti; Yusnani Batubara (Jurnal Al Athfaal, 2023)
The problem in this research is whether the role of health and nutrition can influence the growth and development of early childhood. Meanwhile, the aim of this research is to find out whether health and nutrition are related to early childhood development. This method is library research, the qualitative analysis uses Miles and Huberman model data, data analysis uses the Miles and Huberman cycle which includes data reduction, data models, and verification. Meanwhile, to test the validity of this research, credibility, transferability, dependability and certainty so that the validity of this research can be known. The results of this research are that health and nutrition play an important role in the growth and development of early childhood. Nutrition or nutrition is a component that must be present and its existence is very necessary for the body, especially in the process of physical growth and development, the nervous system and brain, as well as the level of human intellect and intelligence. Fulfilling nutritional needs is the main factor in achieving growth and development results in accordance with genetic potential.